Evaluation of Titanium Based Alloys as Interconnects for the Light Weight SOFC System. (10th July 2019) - Kobayashi, Keiko; Miyata, Ryuichi; Yashiro, Keiji; Takamura, Hitoshi; Yoshimi, Kyosuke; Kawada, Tatsuya; Hashimoto, Shinichi; Okai, Keiichi
Abstract : Ti alloys were evaluated as new candidates for interconnects of a lightweight SOFC which is to be mounted on aircrafts. Oxygen permeation test was performed by flowing air and He gas. No notable oxygen leak was observed. Area specific resistance (ASR) of oxide-scales formed between the alloy the electrode contacts was investigated by impedance spectroscopy. Two different electrodes, Pt and La0.6 Sr0.4 Co0.2 Fe0.8 O3- δ (LSCF), attached on the surface of Ti alloys were tested with time in air at 873 K. Although ASR at the contact with Pt electrode was small, the oxide scale grown under LSCF showed a large ASR increasing with time. After the ASR measurement, cross section between the alloy and the electrode contacts were observed by scanning electron microscope and analyzed by energy-dispersive X-ray spectroscopy. Growth of the oxide scale was found to be promoted by LSCF.